(untitled) (Vietnam Journal of Community Medicine, 2026)
ABSTRACT Objective: To evaluate the outcomes of laparoscopic cholecystectomy for the treatment of acute calculous cholecystitis in elderly patients at Viet Nam – Sweden Uong Bi Hospital. Subjects and Methods: A descriptive cross-sectional study combining retrospective and prospective approaches was conducted on 85 patients aged ≥60 years who were diagnosed with acute calculous cholecystitis and underwent laparoscopic cholecystectomy between June 2022 and June 2025. Results: The mean age was 73.7 ± 6.7 years, with a female-to-male ratio of 1.2:1. All patients had underlying comorbidities, with 91.8% having ≥2 chronic diseases, predominantly cardiovascular disorders (97.6%). According to the Tokyo Guidelines 2018, grade I–II accounted for 84.7% of cases. The mean operative time was 48.3 ± 17.5 minutes. Most procedures utilized three trocars (81.2%). No intraoperative complications were observed. The mean postoperative pain duration was 2.9 days (VAS 4.1), gradually decreasing over 2–5 days. Mean times to first flatus and oral intake were 2.2 and 2.3 days, respectively. The mean hospital stay was 8.9 days. Surgical site infection occurred in 9% of cases. Good outcomes were achieved in 81.2% of patients, with no cases of poor outcomes. Conclusion: Laparoscopic cholecystectomy is a safe and effective method for the treatment of acute calculous cholecystitis in elderly patients.